2003
DOI: 10.1073/pnas.0436218100
|View full text |Cite
|
Sign up to set email alerts
|

Base pairing among three cis-acting sequences contributes to template switching during hepadnavirus reverse transcription

Abstract: Synthesis of the relaxed-circular (RC) DNA genome of hepadnaviruses requires two template switches during plus-strand DNA synthesis: primer translocation and circularization. Although primer translocation and circularization use different donor and acceptor sequences, and are distinct temporally, they share the common theme of switching from one end of the minusstrand template to the other end. Studies of duck hepatitis B virus have indicated that, in addition to the donor and acceptor sequences, three other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
42
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 22 publications
3
42
0
Order By: Relevance
“…More details than is possible to show here can be found in informative schematic representations in references [144,160] .…”
Section: ( + ) -S T R a N D D N A S Y N T H E S I S A N D Circularizamentioning
confidence: 99%
See 1 more Smart Citation
“…More details than is possible to show here can be found in informative schematic representations in references [144,160] .…”
Section: ( + ) -S T R a N D D N A S Y N T H E S I S A N D Circularizamentioning
confidence: 99%
“…Using quantitative genetic techniques, the Loeb laboratory has defined, mostly in DHBV, several such cis-elements on the (-)-DNA [144,[156][157][158][159][160][161] , e.g. 3E, M, and 5E, which are located at both termini and in the middle of pgRNA.…”
Section: ( + ) -S T R a N D D N A S Y N T H E S I S A N D Circularizamentioning
confidence: 99%
“…Therefore, complementarity between the nascent minus-strand and acceptor sequence on the pgRNA is not sufficient for first-strand template switch. Studies of plusstrand DNA synthesis in duck HBV have shown that cis-acting sequences are present on minus-strand DNA that contribute to the subsequent plus-strand synthesis (11,12). It is reasonable to postulate that cis-acting sequences are present on pgRNA that facilitate minus-strand DNA synthesis in HBV.…”
mentioning
confidence: 99%
“…The final product is a partially doublestranded, relaxed circular DNA (rcDNA). Occasionally, one of the translocation steps fails (in situ priming), resulting in a double-stranded linear molecule (17,19,24,25).The C-terminal domain of the core protein plays a crucial role in viral replication. It is rich in arginine residues and contains three serine phosphorylation sites.…”
mentioning
confidence: 99%
“…Notably, however, spliced RNA species containing all sequence elements necessary for packaging and for reverse transcription have been observed in liver tissue and in transfected cells (9,23,(26)(27)(28)(29). Viral DNA synthesis is a highly complex process involving three translocation events of P to priming sites located at the respective 5Ј and 3Ј ends of the template (17). Thus, both ends must be accessible to the encapsidated P protein.…”
mentioning
confidence: 99%